COMPARATIVE ANALYSIS OF PROPOFOL AND PROPOFOL WITH KETAMINE IN AMBULATORY ANESTHESIA PATIENTS: A PROSPECTIVE STUDY - Gaur, Divyansh; Raza, Ali; Gupta, Sachin Kumar; Jayantilal, Shah Raj; Shrikanta (Student’s Journal of Health Research Africa, 2024)
Background The barbiturate class of sedatives and anesthetics has a prolonged half-life. Ambulatory admittance is used for minor procedures like endoscopies that are performed on outpatients. After the surgery is over, the patients can be released from the anesthetic’s effects. Objectives The goal of this research was to compare total intravenous anesthesia in ambulatory anesthesia using propofol alone versus propofol plus ketamine. Materials and methods The study was designed as a prospective study that took place at the Department of Anesthesia, Deen Dayal Upadhyaya Hospital, Delhi, India. The study was conducted for six months. In all, sixty people were invited to participate in the study. Results The induction dosage in both the groups of participants were 2.01±0.13 and 1.58±0.4 respectively in the patient groups that received propofol and propofol plus ketamine. Time to recover from induction dose was found to be highly significant. Conclusion According to this study, propofol and ketamine together provide better hemodynamic stability when compared to propofol since they require less induction and have fewer side effects. Additionally, the duration of pain alleviation following surgery was greater. Recommendations For ambulatory anesthesia, propofol, and ketamine together provide an effective anesthetic with a lower risk of adverse medication reactions; hence, it should be chosen over propofol alone.